Virtual reality in education: global trends, challenges, and impacts—game changer or passing trend? - Samala, Agariadne Dwinggo; Rawas, Soha; Rahmadika, Sandi; Criollo-C, Santiago; Fikri, Ryan; Sandra, Randi Proska (Discover education, 2025)
Virtual reality (VR) has emerged as a transformative technology in education, enabling immersive simulations that foster student engagement and improve knowledge retention. This study presents a bibliometric analysis of global trends, research patterns, and challenges related to the integration of VR in educational contexts. Data were collected from the Science Citation Index Expanded (SCIE), Social Sciences Citation Index (SSCI), and Emerging Sources Citation Index (ESCI) within the Web of Science Core Collection, including only articles also indexed in Scopus to ensure high-quality and comprehensive coverage. Of the 1220 articles published between 2010 and 2024, 97 met the inclusion criteria based on relevance, accessibility, and methodological rigor. We performed keyword analysis, citation analysis, and thematic mapping using RStudio and the Bibliometrix package. The findings indicate that the United States, China, and the United Kingdom are the most active contributors to VR research in education. VR has been applied across diverse learning modalities, enriching both formal and informal educational environments. However, its widespread adoption faces several barriers, including high implementation costs, health and safety concerns, limited curricular integration, and insufficient educator training. Proposed solutions include strategic partnerships with technology providers and the use of cloud-based infrastructures to reduce costs and complexity. This study offers actionable insights for educators, policymakers, and developers, providing a robust, data-driven foundation for the effective and equitable integration of VR in education.